The Effect of Paracetamol on The Development of Chicken Embryos - Saragih, Hendry Tri Sakti Surya Gunawan; Primahesa, Alfian; Oktaviana, Shintia; Setyo, Agnessia Asian Budi; Anisya, Alifia; Allimi, Hayu Swari; Zusrina, Laili Mufli; Saribu, Ruth Liananda Citra Dolok; Nuriliani, Ardaning; Septriani, Nur Indah (Biology, Medicine, & Natural Product Chemistry, 2024)
Paracetamol (N-Acetylaminophenol) is the most widely used over-the-counter drug in the world. Although considered safe for pregnant mothers, there is a concern regarding the teratogenic effect of paracetamol. This study aims to observe the teratogenic effect of paracetamol developing embryos. Using chicken embryos, the embryos were incubated for 48 hours and then injected with paracetamol in 3 concentrations, namely 10 ppm, 15 ppm, and 20 ppm. The control group and treatment group consisted of 3 replicates of fertile embryos. Then, the embryos were incubated again for 48 hours in the incubator. Data analysis was carried out qualitatively by observing any developmental alterations. Results showed that paracetamol caused enlargement of the head and heart edema. Exposure to paracetamol at concentrations of 15 ppm and 20 ppm affects the morphology of chicken embryos, especially the formation of the head and disrupts the process of angiogenesis and normal heart formation, causing bleeding and edema at higher concentrations.